Abordagem laboratorial no diagnóstico da alergia alimentar - Cocco, Renata Rodrigues [UNIFESP] (2007)
OBJCTIVE: Review the available laboratory tests used to assist in the diagnosis of IgE-mediated and non-IgE-mediated food allergy. DATA SOURCES: Papers in English and Portuguese published in PubMed and Embase, in the last ten years. Terms searched were food allergy, diagnose and laboratory, isolated and/or associated. DATA SYNTHESIS: The diagnostic approach to food allergy reactions includes a good medical history, laboratory studies, elimination diets and blinded food challenges. More recently, the use of a quantitative measurement of food-specific IgE antibodies has been shown to be more predictive of symptomatic IgE-mediated food allergy. Food-specific IgE serum levels exceeding the diagnostic values indicate that the patient is greater than 95% likely to experience an allergic reaction if he/she ingests the specific food. Such decision point values have been defined just for some foods and inconsistent results were obtained when allergy to the same food was studied in different centers. Food challenges, in particular the double-blind placebo-controlled food challenge (DBPCFC), represent the most reliable way to establish or rule out food hypersensitivity. CONCLUSIONS: A number of recent developments are improving the predictive value of some laboratory tests for the diagnosis of food allergies. However, to date, no in-vitro or in-vivo test shows full correlation with clinical food allergy and the DBPCFC remains the gold standard for the definitive diagnosis of specific food allergies. There is an urgent need for new and fundamentally improved diagnostic approaches, which must be validated in patients with food allergy confirmed by a positive DBPCFC.